Microvascular decompression for trigeminal neuralgia: A long-term follow-up study - (:unkn) unknown (GEORG THIEME VERLAG KG, 2006)
In this report, we present our experience with microvascular decompression (MVD) as treatment for trigeminal neuralgia (TN) and discuss factors related to recurrence after this procedure. Between 1986 and 2004, 90 patients underwent MVD for treatment of idiopathic TN at the Marmara University Department of Neurosurgery and Marmara University Neurological Sciences Institute. Individuals with atypical and secondary forms of TN were excluded from the study. The patient characteristics, workup findings, observations during surgery, and results of MVD for the 90 cases are reviewed. In 87 (97%) of the patients, exposure of the pontocerebellar angle revealed a vascular structure compressing the trigeminal nerve. In the patients with vascular compression, the problem vessel was an artery in 80 (92%) cases and a vein in 7 (8%) cases. In 77 cases, all symptoms were completely resolved by the operation. Ten patients experienced significant partial relief, and the intensity of the residual pain in these cases was not severe enough to require medication. Three patients experienced no improvement after MVD. There was no mortality associated with MVD in the 90 cases. The findings for our series of 90 patients with TN who underwent MVD indicate that this operation is an effective and reliable treatment for this condition. We recommend MVD as the first-line surgical approach for patients with TN who do not respond to medical management.
Keywords: microvascular decompression; trigeminal nerve; trigeminal neuralgia; NEUROVASCULAR COMPRESSION; NERVE; EXPERIENCE; OPERATIONS; RHIZOTOMY